ANALISIS PENGARUH KUALITAS PELAYANAN MOBILE BANKING DAN KUALITAS PRODUK TABUNGAN IB HIJRAH RENCANA TERHADAP LOYALITAS NASABAH BANK MUAMALAT KANTOR CABANG PEMBANTU TANJUNG PANDAN - Aldi Bahar; Hajar Mukaromah (STAI YAPTIP, 2021)
This study discusses the quality of service in the form of applications and one of the products owned by Bank Muamalat towards customer loyalty. Seeing the phenomenon where many customers consider quality in any way to entrust their finances to a Sharia Bank. This study aims to find out about some of the service qualities that a Sharia bank has. This research is a field research conducted directly on financial institutions, this type of research is descriptive quantitative. Sources of data used in this study came from two sources, namely primary data sources and secondary data which took from primary sources, namely questionnaires and additional sources such as accurate information. The population of this research is 3,500 people whose sample is 5% according to Yount theory. Meanwhile, for sampling using the Non Probability Sampling technique, which is a sampling technique that does not provide equal opportunities or opportunities for each element or member of the population to be selected as samples. The data analysis techniques included the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, t test, F test, and R2 test. The results of this study indicate that the variables of Mobile Banking and Product Quality simultaneously affect customer loyalty at Bank Muamalat KCP Tanjung Pandan